Quantitative phase-contrast confocal microscope - Liu, Changgeng; Marchesini, Stefano; Kim, Myung K. (Optics express, 2014)
We present a quantitative phase-contrast confocal microscope (QPCCM) by combining a line-scanning confocal system with digital holography (DH). This combination can merge the merits of these two different imaging modalities. High-contrast intensity images with low coherent noise, and the optical sectioning capability are made available due to the confocality. Phase profiles of the samples become accessible thanks to DH. QPCCM is able to quantitatively measure the phase variations of optical sections of the opaque samples and has the potential to take high-quality intensity and phase images of non-opaque samples such as many biological samples. Because each line scan is recorded by a hologram that may contain the optical aberrations of the system, it opens avenues for a variety of numerical aberration compensation methods and development of full digital adaptive optics confocal system to emulate current hardware-based adaptive optics system for biomedical imaging, especially ophthalmic imaging. Preliminary experiments with a microscope objective of NA 0.65 and 40 × on opaque samples are presented to demonstrate this idea. The measured lateral and axial resolutions of the intensity images from the current system are ~0.64μm and ~2.70μm respectively. The noise level of the phase profile by QPCCM is ~2.4nm which is better than the result by DH.